2000
DOI: 10.1086/316098
|View full text |Cite
|
Sign up to set email alerts
|

In Sickness and in Health: Risk Sharing within Households in Rural Ethiopia

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(147 citation statements)
references
References 39 publications
7
139
0
1
Order By: Relevance
“…3 Studies examining risk sharing within households find less support for the assumption of cooperative decision making. Dercon and Krishnan (2000) find that poor households in southern Ethiopia do not engage in complete risk sharing; women in these households bear the brunt of adverse shocks. Doss (2001) finds that in Ghana shocks to men's and women's incomes have different effects on household expenditure patterns, suggesting that household members may be concerned about their individual long-term access to resources and that membership in a household is one way, but not the only way, to ensure this access.…”
Section: Empirical Literature On Cooperative and Noncooperative Outcomesmentioning
confidence: 89%
“…3 Studies examining risk sharing within households find less support for the assumption of cooperative decision making. Dercon and Krishnan (2000) find that poor households in southern Ethiopia do not engage in complete risk sharing; women in these households bear the brunt of adverse shocks. Doss (2001) finds that in Ghana shocks to men's and women's incomes have different effects on household expenditure patterns, suggesting that household members may be concerned about their individual long-term access to resources and that membership in a household is one way, but not the only way, to ensure this access.…”
Section: Empirical Literature On Cooperative and Noncooperative Outcomesmentioning
confidence: 89%
“…Central questions addressed in the empirical literature have been whether there is any evidence of complete risk-sharing both in communities in developing country as in a wide variety of settings, including the US and how (partial or complete) risk-sharing is obtained. The tests have generally found that complete risk-sharing has to be rejected, including in the US, in communities in India, in extended families in the PSID or even within nuclear households in Ethiopia (Townsend 1994, Hayashi et al 1996, Dercon and Krishnan 2000b. Nevertheless, the evidence is consistent with partial risk-sharing.…”
Section: Informal Risk-sharing and Safety Netsmentioning
confidence: 99%
“…Behrman and Deolalikar (1990), using data on individual nutrient intakes from India, report that estimated price and wage elasticities of intakes are substantially and significantly higher for females than for males, suggesting that women and girls share a disproportionate burden of rising food prices. Dercon and Krishnan (2000b) test risk-sharing within rural households in Ethiopia. Adult nutrition is used to investigate whether individuals are able to smooth their consumption and within the household over the seasons.…”
Section: Risk Household Responses and Consequencesmentioning
confidence: 99%
“…Dercon and Krishnan (2000) find that women in poor households have especially little bargaining power and so bear the brunt of illness shocks. Liquidity-constrained households in their sample are compelled to allocate scarce resources to those members who are more productive or more likely to survive.…”
Section: Bargaining and Illnessmentioning
confidence: 96%